The Predictive Value of Mean Platelet Volume for Liver Fibrosis in Children With Chronic Liver Diseases - Seyed Mohsen Dehghani (Zabol University of Medical sciences, 2020)
Introduction: Almost all causes of chronic liver damage can culminate in liver fibrosis and ultimately cirrhosis. Studies have suggested a relationship between mean platelet volume (MPV) and liver fibrosis; however, this needs confirmation by further studies. We here assessed the predictive value of MPV for liver fibrosis in children with chronic liver diseases. Methods: In this study, children <18 years old with chronic liver diseases referred to the Nemazee Hospital of Shiraz during 2013-2016 were studied. The patients underwent liver biopsy for assessing liver fibrosis. Statistical analyses were conducted in SPSS 23. Results: From 368 studied children, 52.2% were boys. The patients’ mean age was 4.5±3.9 years old. Most patients had grade 6 fibrosis (36.7%). Cryptogenic (42.7%) was the most common cause of chronic liver disease, and jaundice was the most prevalent clinical presentation (53%). There was a significant association between the liver fibrosis and MPV (P=0.025). Conclusion: MPV was significantly different between patients with different severities of liver fibrosis. However, assigning an appropriate cut off value to distinguish different degrees of fibrosis requires more studies.